Development of an integrated framework for minimal cut set enumeration in constraint-based models - Vieira, Vítor (2016)
Under the realm of in silico Metabolic Engineering, pathway analysis approaches to strain optimization have shown a large potential as tools capable of providing an unbiased view over metabolic models. Most of these methods were difficult or impossible to use due to their heavy computational needs, since they are based in the calculation of elementary modes/minimal cut sets in large networks. However, a recent method (MCSEnumerator) has enabled the application of these approaches to genome-scale metabolic models. This work proposes a new software tool where this method is implemented in a novel Java library, that provides support for a plugin for the OptFlux metabolic engineering platform. Together, these tools implement the routines necessary for the calculation of minimal cut sets and their use to provide strain optimization methods. The aim is to provide an open-source software tool that includes an intuitive graphical user interface, thus facilitating its use by the community.